2016
DOI: 10.1016/j.jnt.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotomic coefficients: gaps and jumps

Abstract: We improve several recent results by Hong, Lee, Lee and Park (2012) on gaps and Bzdȩga (2014) on jumps amongst the coefficients of cyclotomic polynomials. Besides direct improvements, we also introduce several new techniques that have never been used in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The fact that g(F p,q ) = p − 1 was proven in [3] for binary cyclotomic polynomials Φ pq and in [6] for semi-group polynomials. In [2,7], it is proven that the number of maximum gaps in binary cyclotomic polynomials is 2⌊q/p⌋. Our description in terms of words easily entails the inequality g(F p,q ) p − 1 and proves that there are, at least, 2⌊q/p⌋ maximum gaps.…”
Section: Conclusion and Further Workmentioning
confidence: 76%
“…The fact that g(F p,q ) = p − 1 was proven in [3] for binary cyclotomic polynomials Φ pq and in [6] for semi-group polynomials. In [2,7], it is proven that the number of maximum gaps in binary cyclotomic polynomials is 2⌊q/p⌋. Our description in terms of words easily entails the inequality g(F p,q ) p − 1 and proves that there are, at least, 2⌊q/p⌋ maximum gaps.…”
Section: Conclusion and Further Workmentioning
confidence: 76%
“…of jumps of ternary cyclotomic coefficients studied by the author [3] and Camburu, Ciolan, Luca, Moree and Shparlinski [5].…”
Section: Resultsmentioning
confidence: 99%
“…Yet another short proof was given by Kaplan (2016) [30, End of Section 2.1]. Furthermore, Camburu, Ciolan, Luca, Moree, and Shparlinski (2016) [30] determined the number of maximum gaps of Φ pq (X), and the existence of particular gaps in the case in which q ≡ ±1 (mod p). The following theorem collects these results [30,58,88].…”
Section: Binary Cyclotomic Polynomialsmentioning
confidence: 99%
“…Bzdȩga [26] proved that J n > n 1/3 for all ternary integers n. As a corollary, θ n > n 1/3 . Also, he showed that Schinzel Hypothesis H implies that for every ε > 0 we have J n < 10n 1/3+ε for infinitely many ternary integers n. Camburu, Ciolan, Luca, Moree, and Shparlinski (2016) [30] gave an unconditional proof that J n < n 7/8+ε for infinitely many ternary integers n.…”
Section: Jump One Propertymentioning
confidence: 99%